2013
DOI: 10.1002/chem.201300579
|View full text |Cite
|
Sign up to set email alerts
|

A Redox‐Mediator‐Free Solar‐Driven Z‐Scheme Water‐Splitting System Consisting of Modified Ta3N5 as an Oxygen‐Evolution Photocatalyst

Abstract: Tantalum nitride (Ta3N5) modified with various O2-evolution cocatalysts was employed as a photocatalyst for water oxidation under visible light (λ>420 nm) in an attempt to construct a redox-mediator-free Z-scheme water-splitting system. Ta3N5 was prepared by nitriding Ta2O5 powder under a flow of NH3 at 1023-1223 K. The activity of Ta3N5 for water oxidation from an aqueous AgNO3 solution as an electron acceptor without cocatalyst was dependent on the generation of a well-crystallized Ta3N5 phase with a low den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 41 publications
0
84
0
Order By: Relevance
“…[1][2][3] Many of semiconducting metal oxides such as TiO 2 and ZnO are, however, inactive in visible light-induced photocatalytic reactions because of their wide bandgap energy and improper band positions. [4] To circumvent the drawbacks of metal oxides, various attempts including chemical substitution and surface sensitization have been made to provide visible light harvesting ability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Many of semiconducting metal oxides such as TiO 2 and ZnO are, however, inactive in visible light-induced photocatalytic reactions because of their wide bandgap energy and improper band positions. [4] To circumvent the drawbacks of metal oxides, various attempts including chemical substitution and surface sensitization have been made to provide visible light harvesting ability.…”
Section: Introductionmentioning
confidence: 99%
“…Many works studied different connection modes of Z‐scheme photocatalytic systems 13, 17, 18, 19, 20, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, …”
Section: Introductionmentioning
confidence: 99%
“…This two-step excitation process, the so-called "Z-scheme", has been widely studied in both fundamental and applied fields of research [2][3][4][5]. In the past decade, various systems capable of Z-scheme water splitting (Figure 1b), such as Pt or Ru/SrTiO 3 :Rh-Fe 3+ /Fe 2+ -WO 3 , BiVO 4 , or Bi 2 MoO 6 [6,7], Pt/TaON-IO 3´/ I´-PtO X /WO 3 or RuO 2 /TaON [8,9], Pt/ZrO 2 /TaON-IO 3´/ I´-Ir/TiO 2 /Ta 3 N 5 or RuO 2 /TaON [10,11], and other systems [12][13][14][15], have been reported. Our research group has also reported Z-scheme water splitting using porphyrin-dye-modified inorganic semiconductors, such as KTa(Zr)O 3 [16][17][18], GaN:ZnO [19] and TaON [20].…”
Section: Introductionmentioning
confidence: 99%